Efficacy, safety and feasibility of treatment of chronic HCV infection with directly acting agents in hematopoietic stem cell transplant recipients – Study of infectious diseases working party of EBMT. Issue 1 (January 2022) - Mikulska, Malgorzata; Knelange, Nina; Nicolini, Laura Ambra; Tridello, Gloria; Santarone, Stella; Di Bartolomeo, Paolo; de la Camara, Rafael; Cuéllar, Clara; Velardi, Andrea; Perruccio, Katia; Ljungman, Per; Zaucha, Jan; et al.
Highlights: The vast majority of HSCT recipients is eligible for HCV DAA-based treatment. DAAs are safe and effective in HSCT recipients. DAAs premature discontinuation was rare and not related to side effects. Abstract: Objectives: Limited data is available on HCV directly acting agents (DAAs) in haematopoietic stem cell transplant (HSCT) recipients. This study aimed at reporting the characteristics, treatment practices and treatment efficacy in HSCT recipients with chronic HCV. Methods: Prospective observational study from EBMT Infectious Diseases Working Party (IDWP). Patients with chronic HCV infection were included. Results: Between 12/2015 and 07/2018, 45 patients were included: male in 53%; median age 49 years (range, 8–75); acute leukaemia in 48.9%, lymphoma in 17.7%, non-malignant disorders in 22.3%; allogeneic HSCT in 84%; 77.8% no immunosuppressive treatment. Genotypes 1, 2, 3 and 4 were detected in 54.5%, 20.5%, 13.6% and 11.4%, respectively; advanced fibrosis in 40%, including cirrhosis in 11.4%. Overall, 37 (82.2%) patients received DAAs, at a median of 8.4 years after HSCT (16.2% within 6 months from HSCT). Sofosbuvir-based treatment was given to 62.2%. Thirty-five patients completed planned treatment course, with sustained virological response (SVR) of 89.1%, and 94.3% (33/35) in those who completed the treatment. Side effects possibly related to DAAs were reported in 5 (14%) and did not require treatment discontinuation. Conclusions: DAAs treatment was effective, safe and feasible in this cohort of mainly allogeneic HSCT recipients with mild/moderate liver damage.